A questão da saúde dos trabalhadores na perspectiva histórico-ontológica - Souza, Diego de Oliveira (2012)
This dissertation is a study on the issue of workers' health, in order to analyze it into its essential elements. The interest in this object arose from the author's training in the specialized field occupational health and especially for his concern with the problems faced by the working class under the aegis of dehumanizing and destructive character of capital. This is a bibliographic research conducted at 2011 and 2012 and based on marxian ontological perspective. The dissertation is divided into four chapters: the first describes the contemporary dimension of the problem studied; the second presents the ontogenetic process of the issue; the third discusses over its historical evolution in monopoly capitalism; and the fourth evinces its essence, its origin, its characteristics and its social function. In the end, challenges the conception that the issue of workers' health is a process of cause-consequence between work and health, with its foundations in the biological sphere.